2014
DOI: 10.4103/0331-3131.141021
|View full text |Cite
|
Sign up to set email alerts
|

Short term heart rate variability for early assessment of autonomic neuropathy in patients with type 2 diabetes mellitus: A comparative cross-sectional study

Abstract: A B S T R A C TBackground: Cardiovascular autonomic diabetic neuropathy (CADN) is an important diabetes-associated complication. Reduced heart rate variation is the earliest indicator of CADN. Aims: The aim was to study the prospect of using short term heart rate variability (HRV) analysis for early diagnosis of CADN. Settings and Design: The type of this study was hospital-based comparative cross-sectional study. Materials and Methods: A total of 30 asymptomatic, type 2 diabetic male patients with duration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 15 publications
3
5
0
Order By: Relevance
“…Similar results were reported by other studies. 17,[24][25][26][27][28] These results of this study did not observe any expected significant changes about autonomic status when compared between patients and control even after performing SR by the patients.…”
Section: Discussionsupporting
confidence: 38%
“…Similar results were reported by other studies. 17,[24][25][26][27][28] These results of this study did not observe any expected significant changes about autonomic status when compared between patients and control even after performing SR by the patients.…”
Section: Discussionsupporting
confidence: 38%
“…Reduced HRV is the earliest sign of CAN 2,[5][6][7][8] . Decline in HRV in T2DM was seen in several studies 3,[9][10][11][12] . Despite the unclear nature of association between the duration of diabetes and autonomic dysfunction 13 , many studies observed the existence of relationship between these two 3,7,9,[14][15] .…”
Section: Introductionmentioning
confidence: 98%
“…Nevertheless, these tests only detect symptomatic or clinical CAN [4,8] which may not be sensitive enough to detect subtle abnormalities in cardiac autonomic nerve activity [9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, reduced HRV has been recognized as the earliest sign of CAN [9,11,[13][14][15][16][17]. 5 minutes HRV test, such as 24 hrs HRV measurement, is a reliable, convenient, and economically practicable technique for detecting autonomic dysfunction [4,[9][10]18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation